American Iron, 1607-1900 - Gordon, Robert B. (Robert Boyd), 1929-; Project Muse. (Baltimore, Md. : Johns Hopkins University Press, 2019)
By applying their abundant natural resources to ironmaking early in the eighteenth century, Americans soon made themselves felt in world markets. After the Revolution, ironmakers supplied the materials necessary to the building of American industry, pushing the fuel efficiency and productivity of their furnaces far ahead of their European rivals.
In American Iron, 1670-1900, Robert B. Gordon draws on recent archaeological findings as well as archival research to present an ambitious, comprehensive survey of iron technology in America from the colonial period to the industry's demise at about the turn of the twentieth century. Closely examining the techniques - the "hows"--Of ironmaking in its various forms, Gordon offers new interpretations of labor, innovation, and product quality in ironmaking, along with the industry's environmental consequences. He shows the high level of skills required to ensure efficient and safe operation of furnaces and to improve the quality of iron product. By mastering founding, fining, puddling, or bloom smelting, ironworkers gained a degree of control over their lives not easily attained by others
1. Iron -- 2. Ore, Fuel, and Other Natural Resources -- 3. The Rise of American Iron, 1720-1860 -- 4. Smelting with Charcoal -- 5. Converting Pig Iron to Wrought Iron -- 6. Coal-Fired Blast Furnaces -- 7. Steel -- 8. Shaping Iron and Steel -- 9. Iron Quality -- 10. Ironmaking Eclipsed, 1860-1900 -- 11. The Industrial Archaeology of Iron -- Appendix A Metallography -- Appendix B Iron Production Data.
The text of this book is licensed under a Creative Commons Attribution-NonCommercial-No derivatives 4.0 International License.
Open access edition supported by the National Endowment for the Humanities / Andrew W. Mellon Foundation Humanities Open Book Program.
Description based on print version record.
Keywords: Iron -- Metallurgy; Iron-works.; Usines siderurgiques -- Amerique du Nord -- Histoire -- 18e siecle; Usines siderurgiques -- Amerique du Nord -- Histoire -- 19e siecle; Fer -- Metallurgie -- Histoire -- 18e siecle; Fer -- Metallurgie -- Histoire -- 19e siecle; Iron-works -- North America -- History -- 18th century; Iron-works -- North America -- History -- 19th century; Iron -- Metallurgy -- History -- 18th century; Iron -- Metallurgy -- History -- 19th century; North America; History; Electronic books